Two Sizes May Fit All: Promoting Healthier Choices Through Regulatory Fit in Risk Communications - da Silva Costa, Adriano; Gaspar, Rui (Recent Patents on Food, Nutrition & Agriculture, 2018)
Aims and Background: For consumers to make healthy informed decisions (e.g. choose a low nutritional risk food product), they need to receive and exchange information with experts, health authorities, health and risk communicators and other interest groups. However, communicators often face the challenge that consumers avoid such information and have a low engagement with health and risk communication activities. This often results from a lack of consideration of consumers' characteristics and communications customization to them. Methods: A potential approach to increase engagement with communications is providing information that fits consumers' need and goals, particularly their regulatory orientation. We propose that such customization can be applied within a Mental Models' Approach operationalized through a recently patented Mental Modeling Technology PlatformTM (US9262725B2). Results: Drawing results from psychological science and particularly Regulatory Focus Theory, communications can be customized to two global individual's goal orientation: 1) Promotion focus; 2) Prevention Focus. Communications customized into a promotion orientation (vs. prevention orientation) should make salient gains/positive consequences (vs. losses/negative consequences). Regulatory orientation should be measured in Mental Models Approach step two and message customization in step three (communication design). Conclusion: The role of individual psychological factors which influence food perception and choice should be considered in future studies/interventions to promote healthier decisions. Those responsible for designing mass dissemination messages and/or public health interventions, may benefit from using regulatory fit to facilitate behavior change, particularly when cost-effective personalized bidirectional communications are not possible.
Keywords: regulatory focus